2007
DOI: 10.1002/hed.20546
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineered prefabricated vascularized flaps

Abstract: Background. Microvascular free tissue transfer has become increasingly popular in the reconstruction of head and neck defects, but it also has its disadvantages. Tissue engineering allows the generation of neo-tissue for implantation, but these tissues are often avascular. We propose to combine tissue-engineering techniques together with flap prefabrication techniques to generate a prefabricated vascularized soft tissue flap.Methods. Human dermal fibroblasts (HDFs) labeled with fluorescein diacetate were stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, an in-built vascular network can both recapitulate the hierarchical organization of natural vasculatures and improve their ability to withstand intraoperative trauma. Already, engineered vascularised flaps are gaining increasing popularity within the scientific arena [ 24 , 25 ], and the authors propose that it may only be a matter of time before the jump from bench to bedside (or, more accurately, theatre) becomes a feasible reality. Until then, we must strive to further analyse the associated complications of current flap transfers, not least to understand how to best fashion the next generation of tissue-engineered free flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an in-built vascular network can both recapitulate the hierarchical organization of natural vasculatures and improve their ability to withstand intraoperative trauma. Already, engineered vascularised flaps are gaining increasing popularity within the scientific arena [ 24 , 25 ], and the authors propose that it may only be a matter of time before the jump from bench to bedside (or, more accurately, theatre) becomes a feasible reality. Until then, we must strive to further analyse the associated complications of current flap transfers, not least to understand how to best fashion the next generation of tissue-engineered free flaps.…”
Section: Discussionmentioning
confidence: 99%
“…1). e majority of these involved complex defects secondary to sarcoma reconstruction (42) or trauma and open fractures (25).…”
Section: Methodsmentioning
confidence: 99%
“…Different strategies such as the prevascularization of the implant or the use of angiogenic growth factors have been adopted. Recently, arteriovenous loops and bundles have been proposed to enhance the vascularization of different materials such as fibrin gel,1, 2 basement membrane gel or Matrigel,3 polylactic‐ co ‐glycolic acid (PLGA)‐collagen mesh,4 and collagen sponges 5. One of the advantages is that this arteriovenous loop rapidly induces an angiogenesis process, which takes place mainly at the venous side of the loop, as recently demonstrated 6.…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages is that this arteriovenous loop rapidly induces an angiogenesis process, which takes place mainly at the venous side of the loop, as recently demonstrated 6. Moreover, it has been shown that the presence of fibroblasts in a PLGA‐collagen scaffold (CS) supplied by an arteriovenous loop leads into both angiogenesis and collagen formation 4…”
Section: Introductionmentioning
confidence: 99%